2022
DOI: 10.2166/wcc.2022.176
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of SN-SPI and SPI and the trend assessment of drought using the XI correlation technique over Iran

Abstract: In recent decades, human activities such as the excessive production of carbon dioxide gas, deforestation, overexploitation of natural resources, and so on have caused changes in the climate regimes and occurrence frequency of droughts. Thus, the investigation of the trend of changes in drought can be effective in better understanding the drought condition and also more properly managing the adverse effects of drought. Therefore, in this study, the trend of changes in drought was assessed based on the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In contrast, precipitation assessment of the Weihe River basin in China indicates that 1960-2970 and 1980-1990 were two wet decades, where precipitation was 5.51% higher than the long-term average precipitation [49]. Similarly, a study from 1967-2019 in Iran explained that the SPI for the observed stations decreased [50]. SPI 3 projections in the Pacific region of Colombia between 2022 and 2040 reported increased wetness under both RCP 4.5 and RCP 8.5.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, precipitation assessment of the Weihe River basin in China indicates that 1960-2970 and 1980-1990 were two wet decades, where precipitation was 5.51% higher than the long-term average precipitation [49]. Similarly, a study from 1967-2019 in Iran explained that the SPI for the observed stations decreased [50]. SPI 3 projections in the Pacific region of Colombia between 2022 and 2040 reported increased wetness under both RCP 4.5 and RCP 8.5.…”
Section: Discussionmentioning
confidence: 93%